Effects of periodization on strength and muscle hypertrophy in volume-equated resistance training programs: a systematic review and meta-analysis - Moesgaard, L.; Beck, M. M.; Christiansen, L.; Aagaard, P.; Lundbye-Jensen, J. (Sports Medicine, 2022)
Background: In resistance training, periodization is often used in an attempt to promote development of strength and muscle hypertrophy. However, it remains unclear how resistance training variables are most effectively periodized to maximize gains in strength and muscle hypertrophy. Objective: The aims of this study were to examine the current body of literature to determine whether there is an effect of periodization of training volume and intensity on maximal strength and muscle hypertrophy, and, if so, to determine how these variables are more effectively periodized to promote increases in strength and muscle hypertrophy, when volume is equated between conditions from pre to post intervention. Methods: Systematic searches were conducted in PubMed, Scopus and SPORTDiscus databases. Data from the individual studies were extracted and coded. Meta-analyses using the inverse-variance random effects model were performed to compare 1-repetition maximum (1RM) and muscle hypertrophy outcomes in (a) non-periodized (NP) versus periodized training and (b) in linear periodization (LP) versus undulating periodization (UP). Subgroup analyses examining whether results were affected by training status were performed. Meta-analyses of other periodization model comparisons were not performed, due to a low number of studies. Results: Thirty-five studies met the inclusion criteria. Results of the meta-analyses comparing NP and periodized training demonstrated an overall effect on 1RM strength favoring periodized training (ES 0.31, 95% confidence interval (CI) [0.04, 0.57]; Z = 2.28, P = 0.02). In contrast, muscle hypertrophy did not differ between NP and periodized training (ES 0.13, 95% CI [-0.10, 0.36]; Z = 1.10, P = 0.27). Results of the meta-analyses comparing LP and UP indicated an overall effect on 1RM favoring UP (ES 0.31, 95% CI [0.02, 0.61]; Z = 2.06, P = 0.04). Subgroup analyses indicated an effect on 1RM favoring UP in trained participants (ES 0.61, 95% CI [0.00, 1.22]; Z = 1.97 (P = 0.05)), whereas changes in 1RM did not differ between LP and UP in untrained participants (ES 0.06, 95% CI [-0.20, 0.31]; Z = 0.43 (P = 0.67)). The meta-analyses showed that muscle hypertrophy did not differ between LP and UP (ES 0.05, 95% CI [-0.20, 0.29]; Z = 0.36 (P = 0.72)). Conclusion: The results suggest that when volume is equated between conditions, periodized resistance training has a greater effect on 1RM strength compared to NP resistance training. Also, UP resulted in greater increases in 1RM compared to LP. However, subgroup analyses revealed that this was only the case for trained and not previously untrained individuals, indicating that trained individuals benefit from daily or weekly undulations in volume and intensity, when the aim is maximal strength. Periodization of volume and intensity does not seem to affect muscle hypertrophy in volume-equated pre-post designs. Based on this, we propose that the effects of periodization on maximal strength may instead be related to the neurophysiological adaptations accompanying resistance training.